Pengaruh Penambahan Kombinasi Cacing Tanah (Lumbricus rubellus) dan Singkong (Manihot esculenta) pada Pertumbuhan dan Presentase Moulting Lobster Air Tawar (Cherax quadricarinatus) - Milda, Nurlatipa; Heriansah, Heriansah; Basir, Buana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2024)
Freshwater lobster (Cherax quadricarinatus) is a type of crustacean that has relatively fast growth, relatively easy reproduction and handling, is omnivorous and has a morphology similar to sea lobster so that it is in demand by consumers. This study aims to determine the effect of the use of a combination of earthworms and cassava feed on the growth and number of freshwater lobster moulting. The research method used is a Completely Randomized Design (CRD) with five treatments and three replications. Treatment A = 100% earthworms, B = 100% cassava, C = 75% earthworms + 25% cassava, D = 50% earthworms + 50% cassava, D = 25% earthworms + 75% cassava. The results of the study showed that the highest average Absolute Weight Gain (PBM) was obtained in treatment B (2.33 g), followed by treatment D (1.95 g), followed by treatment A (1.85 g), followed by treatment E (1.84) and the lowest in treatment C (1.76 g). The highest average Specific Growth Rate (SGR) was obtained in treatment B feed (4.09%), followed by treatment D (3.83%), followed by treatment A (3.77%), followed by treatment C (3.69%) and the lowest in treatment E (3.60%). The highest Absolute Length Gain (PPM) was obtained in feed B (1.87 cm), followed by treatment A & E feed (1.84 cm), followed by treatment D feed (1.82 cm) and the lowest in treatment C feed (1.78 cm). Survival between consecutive treatments (A=83.33%, B=90%, C=80%, D=80%, E=83.33%). The number of moulting between consecutive treatments (A=9.33%, B=10%, C=9%, D=8.33%, E=8%). The results of the analysis of variance showed that the combination of feed had no significant effect (P>0.05) on PBM, LPS and PPM of freshwater lobsters.